2014
DOI: 10.1190/geo2013-0196.1
|View full text |Cite
|
Sign up to set email alerts
|

Curvatures and inhomogeneities: An improved common-reflection-surface approach

Abstract: Multiparameter stacking is an important tool to obtain a first reliable time image of the subsurface. In addition, it provides wavefield attributes, which form the basis for many important applications. The quality of the image and the attribute estimates relies heavily on the accuracy of the traveltime moveout description. The commonly used hyperbolic common-reflectionsurface (CRS) operator reduces to the NMO hyperbola in the common-midpoint gather. Its accuracy, however, depends on the curvature of the refle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 24 publications
(52 reference statements)
0
31
0
Order By: Relevance
“…The use of zero-offset attributes obtained from a global optimization scheme with improved conflicting dip handling (Walda and Gajewski, 2015) has increased the quality of our results. Also, the application of non-hyperbolic operators such as i-CRS (Schwarz et al, 2014b) may lead to further improvement. Future work also includes the extension of the decomposition principle to 3D.…”
Section: Discussionmentioning
confidence: 98%
“…The use of zero-offset attributes obtained from a global optimization scheme with improved conflicting dip handling (Walda and Gajewski, 2015) has increased the quality of our results. Also, the application of non-hyperbolic operators such as i-CRS (Schwarz et al, 2014b) may lead to further improvement. Future work also includes the extension of the decomposition principle to 3D.…”
Section: Discussionmentioning
confidence: 98%
“…Processing the data with the i‐CRS operator (e.g., Schwarz et al . ) might improve the determination of wavefield attributes since it better fits diffractions. High‐quality attributes will result in more reliable time migration velocities, improved NIP wave tomography, and better pre‐stack data enhancement opportunities.…”
Section: Discussionmentioning
confidence: 99%
“…Following the works of de Bazelaire (1988) and Höcht et al (1999), Schwarz et al (2014aSchwarz et al ( , 2015 found that all higher-order CRS-type stacking operators, including multifocusing (Gelchinsky et al, 1999), can be formulated in terms of the CRS attributes in two different ways, one accounting for overburden heterogeneity by the application of a constant slowness shift, the other, in correspondence with de Bazelaires shifted hyperbola, by a constant shift of the reference time. According to Höcht et al (1999) and Schwarz et al (2014b), both mechanisms can be related to the CRS attributes via Eqs (2) and…”
Section: Crs-based Passive Localizationmentioning
confidence: 99%
“…Alongside the co-existing multifocusing approach and the estimation of local event slopes (Fomel, 2007), several higher-order CRS formulations have been introduced in recent years (Landa et al, 2010;Fomel and Kazinnik, 2013;Schwarz et al, 2014b). By extending the work of de Bazelaire (1988) and Höcht et al (1999), Schwarz et al (2014aSchwarz et al ( , 2015 demonstrated that all these higher-order expressions, including the commonly used hyperbolic CRS operator, can either be formulated for the optical projection or an effective analog of the true kinematics of the wave propagation.…”
Section: Introductionmentioning
confidence: 98%